Optimization Algorithms - Examples - Jan Valdman (IntechOpen, 2018)
This book presents examples of modern optimization algorithms. The focus is on a clear understanding of underlying studied problems, understanding described algorithms by a broad range of scientists and providing (computational) examples that a reader can easily repeat.
English
Keywords: Mathematical Optimization; Physical Sciences; Engineering and Technology; Mathematics; Applied Mathematics